1995
DOI: 10.1002/(sici)1522-712x(1995)1:6<326::aid-igs4>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of gray matter structures from MRI to improve the segmentation of white matter lesions

Abstract: The segmentation of MRI scans of patients with white matter lesions (WML) is difficult because the MRI characteristics of WML are similar to those of gray matter. Intensity‐based statistical classification techniques misclassify some WML as gray matter and some gray matter as WML. We developed a fast elastic matching algorithm that warps a reference data set containing information about the location of the gray matter into the approximate shape of the patient's brain. The region of white matter was segmented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 16 publications
0
94
0
Order By: Relevance
“…Our laboratory has had extensive experience with image-based matching models for a variety of brain matching applications (Warfield et al, 1995;Warfield, 1996;Nakajima et al, 1997;Hata et al, 1998;Warfield et al, 1999;Ferrant et al, 1999b;Hata et al, 2000;Kaus, 2000;Ruiz-Alzola et al, 2001;Rexilius and Warfield, 2001). However, in the context of intraoperative brain matching, such methods have not yet been able to provide a robust and clinically applicable solution.…”
Section: Intraoperative Registration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has had extensive experience with image-based matching models for a variety of brain matching applications (Warfield et al, 1995;Warfield, 1996;Nakajima et al, 1997;Hata et al, 1998;Warfield et al, 1999;Ferrant et al, 1999b;Hata et al, 2000;Kaus, 2000;Ruiz-Alzola et al, 2001;Rexilius and Warfield, 2001). However, in the context of intraoperative brain matching, such methods have not yet been able to provide a robust and clinically applicable solution.…”
Section: Intraoperative Registration Methodsmentioning
confidence: 99%
“…This means we can use segmentation approaches that are robust and accurate but are time consuming and hence impractical to use in the operating room. In our laboratory, preoperative data is segmented with a variety of manual (Gering et al, 1999), semi-automated (Kikinis et al, 1992) or automated (Warfield et al, 1995Kaus et al, 2000) approaches. We select the most robust and accurate approach available for a given clinical application.…”
Section: Preoperative Segmentationmentioning
confidence: 99%
“…Warfield et al (10,11) combined elastic atlas registration with statistical classification. Elastic registration of a brain atlas helped to mask the brain from surrounding structures.…”
Section: Introductionmentioning
confidence: 99%
“…This may be satisfactory when the data to be visualized has already been segmented, e.g. using accurate statistical methods (Wells et al, 1996a) (Warfield et al, 1995), since the model surfaces have been defined. The time penalty for segmentation, whether manual or semi-automatic, and model generation is tolerated to gain real time performance during visualization.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that it is possible to perform pre-operative segmentation by elastic matching of surfaces e.g. (Warfield et al, 1995). However, for intraoperative segmentation and virtual surgery simulation, physical tissue modeling using voxels is being advocated (Gibson, 1997) -hence the need for volume graphics.…”
Section: Introductionmentioning
confidence: 99%